Manajemen Pondok Pesantren dalam Meningkatkan Pendidikan Kewirausahaan Siswa - Yaqutunnafis, Lale; Nurmiati, Nurmiati (Universitas muhammadiyah palembang, 2021)
The purpose of this study was to find out the management of Islamic boarding schools in improving student entrepreneurship education at Darul Kamal Islamic Boarding School, Kembang Kerang, East Lombok. The research method used is a qualitative research method. The research data is described or described in the form of a description according to the actual situation. Data collection techniques were carried out by making interviews, observations and documentation. Data analysis was carried out logically and systematically starting from data reduction, displaying data and providing conclusions. The results of this study indicate that the management of Islamic boarding schools in improving student entrepreneurship education at Ponpes Darul Kamal NW Kembang Kerang Lombok Timur begins with planning, organizing, actuating and controlling to identify and align activities or programs in accordance with the agreed plans and goals to be achieved. together. Activities carried out to improve student entrepreneurship education at Ponpes Darul Kamal NW Kembang Kerang Lombok Timur are carried out by internalizing it through various aspects such as integrated entrepreneurship education in all subjects, integrated entrepreneurship education in extra-curricular activities, integration of entrepreneurship education into materials/books teaching, integrating entrepreneurship education through school culture and integrating entrepreneurship education through local content. In addition, sewing skills, skills in making woven fabrics (slicing woven fabrics), tile making skills, kopsis (student cooperatives), calligraphy making, ingke or plate making crafts, flower pot making crafts from used plastic and internships for students.